In-hospital Major Clinical Outcomes in Patients With Chronic Renal Insufficiency Presenting With Acute Coronary Syndrome: Data From a Registry of 8176 Patients - El-Menyar, Ayman (Mayo Foundation for Medical Education and Research, 2010)
OBJECTIVE: To assess the impact of chronic renal insufficiency (CRI) on in-hospital major adverse cardiac events across the acute coronary syndrome (ACS) spectrum. PATIENTS AND METHODS: From January 29, 2007, through July 29, 2007, 6 adjacent Middle Eastern countries participated in the Gulf Registry of Acute Coronary Events, a prospective, observational registry of 8176 patients. Patients were categorized according to estimated glomerular filtration rate into 4 groups: normal (≥90 mL/min), mild (60-89 mL/min), moderate (30-59 mL/min), and severe CRI (<30 mL/min). Patients' characteristics and in-hospital major adverse cardiac events in the 4 groups were analyzed. RESULTS: Of 6518 consecutive patients with ACS, 2828 (43%) had mild CRI, 1304 (20%) had moderate CRI, and 345 (5%) had severe CRI. In CRI groups, patients were older and had a higher prevalence of hypertension, diabetes mellitus, and dyslipidemia. On admission, these patients had a higher resting heart rate and frequently had atypical and delayed presentations. Compared with the normal estimated glomerular filtration group, CRI groups were less likely to receive antiplatelet drugs, β-blockers, angiotensin-converting enzyme inhibitors, and statins and were less likely to undergo coronary angiography. In-hospital heart failure, cardiogenic shock, and major bleeding episodes were significantly higher in all CRI groups. In multivariate analysis, mild, moderate, and severe CRI were associated with a higher adjusted odds ratio (OR) of death (mild: OR, 2.1; 95% confidence interval [CI], 1.2-3.7; moderate: OR, 6.7; 95% CI, 3.9-11.5; and severe: OR, 12.0; 95% CI, 6.6-21.7). CONCLUSION: Across the ACS spectrum, patients with CRI had a worse risk profile, had more atypical and delayed presentations, and were less likely to receive evidence-based therapy. Chronic renal insufficiency of varying stages is an independent predictor of in-hospital morbidity and mortality.